Chances and challenges—analysis of trends in breast reconstruction. Issue 8 (August 2022) - Yang, Siling; Lin, Xixi; Kückelhaus, Maximilian; Hirsch, Tobias; Klietz, Marie-Luise; Aitzetmüller, Matthias M.
Summary: Introduction: While breast reconstruction has become more and more important within the past decade, research focus areas as well as trends are in constant change. Method: The publications from 2012 to 2021 were retrieved from the Web of Science Core Collection database. CiteSpace visualization analysis software was used to analyze the institutions, countries, regions, categories, and keywords on breast reconstruction research. Result: A total of 3092 articles were selected. The number of articles published in the last 10 years showed an upward trend year by year. The journal " Plastic and Reconstructive Surgery" had the largest number of publications and citations, representing the core journal. The USA had the largest number of publications and the most extensive cooperation with other countries. The research highlights mainly focused on the improvement of surgical techniques, enhancing postoperative recovery, and oncological safety. Conclusion: Over the past decade, research on breast reconstruction has developed steadily, and considerable achievements in the field of surgical techniques, postoperative recovery, and oncological safety were reached. Plastic surgeons should continue to strive for a higher level of evidence study designs, while also recognizing the importance of international and multiple-center cooperation.